Expectations and Reality of International Dispute Resolution - Islami, Muhammad Nur (Jurnal Dinamika Hukum, 2022)
If we look at the provisions contained in the United Nations (especially in its preamble), it will appear that the purpose of the establishment of the United Nations is international peace and security because the United Nations was indeed formed with the background of World War I and II. In contrast, if we pay attention to the provisions of the International Humanitarian Law, the war cannot be prevented. Instead, efforts are made to humanize war. Based on the research, it turns out that the United Nations is not a neutral organization. The United Nations is a political organization run by superpowers, especially The Big Five (United States, Soviet Union, England, France and China). These five countries have veto rights and other advantages so that in international dispute resolution, it often affects the final decisions. Some decisions from ad Hoc Courts, for example, are influenced by these big countries, such as the case of Saddam Hussein. Likewise, the US policy towards cases between Israel and Palestine and terrorism is also evident. Accordingly, this normative research with a case study approach was conducted by taking samples from popular cases in international political issues. The combination of analysis from international provisions with the facts should push the analysis to be more objective.Keywords: International dispute resolution, United Nations